2014
DOI: 10.1144/sp411.3
|View full text |Cite
|
Sign up to set email alerts
|

Potential submerged Aboriginal archaeological sites in South West Arm, Port Hacking, New South Wales, Australia

Abstract: Sealed, submerged palaeoenvironmental deposits date the time range for lithic technologies and enable inferences about cultural change – potentially more accurately than radiometric methods. Sea-level rises triggered by global warming reduce available land, and change the availability of flora, fauna, geological resources, rivers and wetlands. Australian archaeological studies on human adaptation to climate change focus mainly on terrestrial sites, coastal intensification and the few archaeological sites that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The potential for submerged sites on Australia's continental shelves has long been recognized [30][31][32], but the relatively few attempts made to locate such sites have been unsuccessful [33,34]. In several areas stone artefact sites and quarries, and stone-walled fish traps, have been documented in intertidal zones [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The potential for submerged sites on Australia's continental shelves has long been recognized [30][31][32], but the relatively few attempts made to locate such sites have been unsuccessful [33,34]. In several areas stone artefact sites and quarries, and stone-walled fish traps, have been documented in intertidal zones [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…This has recently been recognised through a reengagement with the topic (Nutley et al, 2016;Veth et al, 2017a, Ward et al, 2015. Two distinct strands of work can be seen to have emerged; site specific investigations looking at potential survival of submerged rock shelter that might have been used by prehistoric populations (Nutley, 2014) and landscape/process driven research (Brooke et al, 2017;Ward et al, 2015Ward et al, , 2014 for regions where multiple questions can be answered to be identified allowing for efficient research, with the Dampier archipelago and Barrow island coming to the fore.…”
Section: Australia and South East Asiamentioning
confidence: 99%
“…Despite the difficulty of locating archaeological material, the preservation of Pleistocene to early Holocene sites has been demonstrated in several parts of the world (Masters and Flemming 1983;Benjamin et al 2011;Evans et al 2014;Harff et al 2016;Bailey et al 2017;Flemming et al 2017;. Within the Australian continent, numerous attempts were made to locate underwater Indigenous cultural heritage on the continental shelf (Flemming 1982;Dortch 2002;Nutley 2014;Nutley et al 2016) but to date no direct archaeological evidence had been found until recently (Benjamin et al 2020). This is despite the discovery of Indigenous artefacts in the intertidal zone (McNiven 2004;Ulm 2006;Lewczak and Wilby 2010;Rowland and Ulm 2011;Kreij et al 2018;Dortch et al 2019) and freshwater environments (Dortch 1996;Hudson and Bowler 1997).…”
Section: Introductionmentioning
confidence: 99%